Radiation-Induced Cardiovascular Disease: A Clinical Perspective - Yusuf, Syed Wamique; Venkatesulu, Bhanu Prasad; Mahadevan, Lakshmi Shree; Krishnan, Sunil (Frontiers in Cardiovascular Medicine, 2017)
Cancer survival has improved dramatically and this has led to the manifestation of late side effects of multi-modality therapy. Radiation (RT) to thoracic malignancies results in unintentional irradiation of the cardiac chambers. RT-induced micro-vascular ischemia leads to disruption of the capillary endothelial framework and injury to differentiated myocytes results in deposition of collagen and fibrosis. Coexistence of risk factors of metabolic syndrome and preexisting atherosclerosis in addition to RT exposure results in accelerated occurrence of major coronary events. Hence it becomes pertinent to understand the underlying pathophysiology and clinical manifestations of RT- induced cardiovascular disease to devise optimal preventive and surveillance strategies.